The Role of KDM2B in Regulating Ribosome Biogenesis and mRNA Translation - Anastas, Vollter. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024-05.; Submitted to the Dept. of Genetics.; Advisor: Philip Tsichlis.; Committee: Claire Moore, Karl Munger, and Philip Hinds.; Keywords: Cellular biology, Genetics, and Molecular biology.